Time Dependence of the Open Circuit Potential of Platinum Disk Electrodes in Half Cell Experiments. Issue 7 (1st January 2019) - Reimer, Uwe; Cai, Yun; Li, Ruiyu; Froning, Dieter; Lehnert, Werner
Abstract : The time dependence of the open circuit potential under oxygen and air is characterized by half-cell experiments in the temperature range of 30°C to 80°C. The data is analyzed with the aid of a macroscopic model that captures the effect of a coupled reaction of platinum surface oxidation and the oxygen reduction reaction. The aim of the model is to facilitate an understanding of the principle reactions from an engineering perspective. Two modeling approaches, namely 'gas electrode' and 'flooded electrode', are compared. It can be shown that the difference between the theoretical Nernst potential and open circuit potential can be described by two major effects: gas solubility in the electrolyte and platinum surface oxidation. The fact that platinum surface oxidation does not lead to a 'fully oxidized surface' has strong implications for the design of accelerated stress tests, which is briefly discussed.